Interstitial Lung Disease as an Extraintestinal Manifestation of Crohn’s Disease in the Time of COVID-19: A Rare Case Report and Review of the Literature - Li L; Liu P; Niu X; He C (Dove Medical Press, 2022)
Lin Li,* Pengwei Liu,* Xiaoping Niu, Chiyi He Departments of Gastroenterology, The First Affiliated Hospital of Wannan Medical College, Wuhu, 241001, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaoping Niu; Chiyi He, Departments of Gastroenterology, Yijishan Hospital of Wannan Medical College, Wuhu, 241001, People's Republic of China, Email 47440311@qq.com; hechiyi11@163.comIntroduction: Recently, the extraintestinal manifestations of Crohn's disease (CD) have attracted more and more attention, among which interstitial lung disease (ILD) is a rare extraintestinal manifestation. Clinical presentation is polymorphic and pathogenesis remains unclear. The purpose of this article is to elaborate on these rare extraintestinal manifestations of CD, and the importance of short-term chest computed tomography (CT) for differential diagnosis is emphasized.Case Presentation: A 27-year-old male patient, who is a student, presented with chief complaints of "loose stools for 4 months, intermittent low-grade fever for 1 month". The next day, he developed a high fever with a body temperature of 39.8°C. A chest CT scan revealed multiple patellar ground glass shadows which suggested ILD. In the time of Corona virus disease (COVID-19), novel coronavirus pneumonia was first suspected according to the patient's history and symptoms, but laboratory examinations did not confirm. Colonoscopy showed multiple ulcers between the sigmoid colon to the terminal ileum, and pathology found epithelioid granuloma in submucosa. Moreover, a total gastrointestinal CT angiography showed that segmental leaping thickening of the bowel. Based on the above results, we ultimately made a diagnosis of CD. After using systemic steroid therapy, his fever was quickly relieved, and a follow-up chest CT showed that multiple patellar ground glass shadows were almost completely absorbed. Then, infliximab was used, and a repeat colonoscopy showed that intestinal ulcers were significantly improved.Conclusion: ILD is a rare extraintestinal manifestation of CD and reveals the excellent response to systemic steroid therapy. Manifestations of pulmonary disease associated with IBD are polymorphic; therefore; clinicians should be more vigilant regarding IBD-related ILD, especially when infectious causes have been excluded in the time of COVID-19. For those with ILD related to IBD, a short-term follow-up CT would be crucial.Keywords: Crohn's disease, interstitial lung disease, steroid, infliximab